Survey and Assessment of Covid-19 Pandemic on the Economy of Tra Vinh Province, Viet Nam and Policy Implications - NGUYEN, Ha Hong (Advances in Social Sciences Research Journal, 2021)
This study aims to evaluate the impact of Covid-19 pandemic on the business performance in Tra Vinh province, Viet Nam and suggests a feasible policy to overcome the challenges in the coming time. By collecting secondary data from the surveyed results report, the authors evaluate the impacts of Covid-19 on the business performance in Tra Vinh province via two surveys announced by Tra Vinh Statistical Office in April 2020 and September 2020; at the same time, by the method of evaluation, comparison and analysis, the current affairs and business activities of Tra Vinh province in the Covid-2019 pandemic period will also be effectively assessed; the effects of the epidemic on the business activities of the local enterprises. At the same time, we propose the implications of policies in the coming time, towards the dual goal of "Preventing of pandemic and ensuring the economic growth in Tra Vinh Province".